Deteksi dini kanker payudara dengan pemeriksaan sadari dan pemanfaatan tanaman obat keluarga - Syarinta Adenina; Rulan Adnindya; Nia Savitri Tamzil; Angun Kurnia F; Saniyyah Nur Fadillah; Amira Malikha; Melvin Renaldy; Mohammad Edgar Malikan; Muhammad Ayun Endratamma; Athira Medina; Muhammad Kevin Aprilio (Fakultas Kedokteran Universitas Sriwijaya, 2026)
The high incidence of breast cancer remains a significant public health problem in Indonesia. Breast cancer management is challenging because the disease is generally detected at an advanced stage. In fact, breast self-examination (BSE) is a simple and inexpensive method for the early detection of breast cancer. Early detection and management of breast cancer are expected to reduce mortality rates associated with the disease. A preliminary survey revealed that nearly all members of the FKMT Sukarami women’s study group were unaware of breast self-examination and the use of family medicinal plants (ginger) for breast cancer prevention. Based on these findings, this community service activity aimed to enhance public knowledge and skills in performing breast self-examination and utilizing family medicinal plants. The activities included lectures, discussions, and demonstrations. Evaluation was carried out by measuring knowledge levels before and after the program. The analysis showed an increase in knowledge regarding breast cancer, breast self-examination, and the use of family medicinal plants (ginger) following the educational session.